English for Hospitality: A Representation of Oral Communication Practices in Food and Beverage (F&B) Services in the British Mini-Series “Boiling Point” - Eka Putri, Rahmadila (Universitas Teuku Umar, 2025)
English proficiency constitutes a pivotal competency in the professional hospitality industry, particularly within Food & Beverage (F&B) services, where oral communication significantly influences service quality, customer satisfaction, and overall operational effectiveness. This study examined the representation of English for Hospitality in high-pressure hospitality environments as depicted in British mini-series “Boiling Point” (2023) where linguistic precision, contextual awareness, and pragmatic competence were integral at ensuring effective interactions. Utilizing a descriptive-qualitative research design and purposive sampling, this study investigated verbal exchanges among restaurant staff and customers, focusing on essential communicative functions of order placement, complaint resolution, and small talk through pragmatic strategies. Thematic analysis revealed that effective order placement involved decision-making discourse and mitigated directives, ensuring clarity while minimizing imposition. In handling complaints, service recovery strategies such as explicit apologies, immediate corrective actions, and reassurance were essential for restoring customer trust and maintaining service excellence. Small talk served as a vital interpersonal engagement strategy, fostering rapport, enhancing guest experience, and reinforcing customer loyalty. Furthermore, this research highlighted the pedagogical potential of audiovisual media, particularly films or series, as instructional tools for English for Hospitality education. By bridging the gap between theoretical linguistic instruction and real-world hospitality practices, film-based instruction not only reinforces communicative competence but also cultivates students’ adaptability in professional service interactions through contextualized understanding of industry-specific discourse and cultural expectations. The immersive pedagogical approaches by incorporating film-based instruction, such as simulations and role-playing activities inspired by audiovisual content, can further strengthen learners’ ability to navigate workplace communication challenges. This study also contributes to the broader discourse on English for Specific Purposes (ESP) by demonstrating the efficacy of audiovisual-based learning in vocational education. Lastly, integrating AI-driven simulations and virtual reality into hospitality communication training can refine these methodologies, ensuring that professionals acquire linguistic and pragmatic skills aligned with global service standards.